Profil Penyelesaian Soal Operasi Hitung Perkalian dan Pembagian Bentuk Aljabar Siswa SMP Negeri 18 Model SPMI Palu - Safira Afrilia; Gandung Sugita; Sutji Rochaminah (Universitas Tadulako, 2022)
The purpose of this study is to describe the completion of arithmetic operations, multiplication and division of algebraic forms for students of SMP Negeri 18 SPMI Palu. This type of research is qualitative research. The subjects in this study were 2 students taken from 32 grade VIIA students of SMP Negeri 18 Model SPMI Palu. The results of this study indicate that the completion of students with high mathematical abilities in solving arithmetic operations problems of multiplication and division of algebraic forms, namely: (1) ST writes the given problem, changes the problem using distributive properties so that the results are obtained. But on the results of the ST distributive property, they did not write down the number sign because they forgot to write it down. Then perform multiplication operations, add up similar terms and get the final result, (2) ST writes down the questions given, performs tiered division operations so that the results are obtained. Completion of students with low mathematical ability in solving arithmetic operations problems of multiplication and division of algebraic forms, namely: (1) SR rewrites the given questions, grouping similar terms, operating like terms so that the results are obtained. However, SR incorrectly determines the result of an integer operation. This is due to SR's inaccuracy when operating, (2) SR wrote questions, did not perform tiered division operations so that the results were obtained.